Optical spectral diagnostics of the oxygenation level in periodontal tissues and photodynamic therapy using methylene blue in children with cerebral palsy - Morozova, Natalia S.; Kozlitina, Iuliia A.; Makarov, Vladimir I.; Loschenov, Victor B.; Grinin, Vasiliy M.; Ivanov, Sergey Yu.; Kashtanova, Maria S. (Frontiers in Public Health, 2023)
Dental diseases occur in children with cerebral palsy three times higher than in healthy children. Low values of the unstimulated salivation rate (<0.3 ml per minute), pH and buffer capacity, changes in enzyme activity and sialic acid concentration, as well as increased saliva osmolarity and total protein concentration, which indicates impaired hydration, are the factors in the development of a gingiva disease in case of cerebral palsy. This leads to increased bacterial agglutination and the formation of acquired pellicle and biofilm, leading to the formation of dental plaque. There is a tendency toward an increase in the concentration of hemoglobin and a decrease in the degree of hemoglobin oxygenation, as well as an increase in the generation of reactive oxygen and nitrogen species. Photodynamic therapy (PDT) with the use of photosensitizer methylene blue improves blood circulation and the degree of oxygenation in periodontal tissues, as well as eliminates a bacterial biofilm. Analysis of back diffuse reflection spectra makes it possible to conduct non-invasive monitoring determine tissue areas with a low level of hemoglobin oxygenation for precision photodynamic exposure. Aim To improve the effectiveness of phototheranostics methods using, namely PDT with simultaneous optical-spectral control, for the treatment of gingivitis in children with complex dental and somatic status (cerebral palsy). Methods The study involved 15 children (6-18 y.o.) with various forms of cerebral palsy, in particular, spastic diplegia and atonic-astatic form and with gingivitis. The degree of hemoglobin oxygenation was measured in tissues before PDT and on the 12th day. PDT was performed using laser radiation (λ = 660 nm) with a power density of 150 mW/cm2 with a five-minute application of 0.01% MB. The total light dose was 45 ± 15 J/cm2. For statistical evaluation of the results, a paired Student's t-test was used. Results The paper presents the results of phototheranostics using methylene blue in children with cerebral palsy. An increase in the level of hemoglobin oxygenation from 50 to 67% (p < 0.001) and a decrease in blood volume in the microcirculatory bed of periodontal tissues were shown. Conclusion Photodynamic therapy methods with application of methylene blue make it possible to assess the state of the gingival mucosa tissue diseases objectively in real time, and to provide effective targeted therapy for gingivitis in children with cerebral palsy. There is a prospect that they can become widely used clinical methods.